The robe [videorecording (DVD)] - Koster, Henry, 1905-1988; Ross, Frank, 1904-1990; Maltz, Albert, 1908-1985; Dunne, Philip, 1908-1992; Kaus, Gina, 1893-1985; Burton, Richard, 1925-1984; Simmons, Jean, 1929-2010; Mature, Victor; Rennie, Michael; Robinson, Jay, 1930-2013; Jagger, Dean, 1903-1991; Thatcher, Torin, 1905-1981; et al. (20th Century Fox Home Entertainment, 2013)
Marcellus is a Roman tribune in the time of Christ. He is in charge of the group of men that are assigned to crucify Jesus. After the crucifixion, he becomes drunk and wins Jesus' homespun robe. He becomes tormented by nightmares and delusions after the event. Hoping to find a way to live with what he has done, but still not believing in Jesus, he returns to Palestine to try and learn what he can of the man he killed.